Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Tailored natural deep eutectic solvents for isolation of astaxanthin from Paracoccus carotinifaciens and one-pot synthesis of functional ingredients for biotechnological applications - Cassamo U. Mussagy; Angie V. Caicedo-Paz; Nataly F. Ramos; Antonia C. Diaz; Mateus F. Cubo; Matheus S. Arantes; Nayara P. Lima; Isabela S. Ribeiro; Charles W.I. Haminiuk; Marcelo Franco; Fabiane O. Farias (Bioresource Technology, 2026)

Future at risk? Specialized flagship herbivores threatened by climate change in the Atlantic Rainforest - Juliane M.F. Bellaver; Diego Hoffmann; Matheus S. Lima-Ribeiro; Lucas A. Kaminski; Ana C.V. Pires; Leandra Bordignon; Geraldo W. Fernandes; Helena P. Romanowski (Journal for Nature Conservation, 2025)

Seasonality and desertification drove the global extinction of megafauna in the late Quaternary - Maurício E. Graipel; Matheus S. Lima-Ribeiro; Jorge J. Cherem; Paul R. Momsen Miller; José A.F. Diniz-Filho; Nilton C. Cáceres (Quaternary Science Reviews, 2024)

Language bias, not knowledge shortfall, underestimates the evidence of megafauna kill sites in South America - Hugo Bampi; João Carlos Pires-Oliveira; Omar Loyola-Bartra; Matheus S. Lima-Ribeiro (Journal of South American Earth Sciences, 2024)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Implications of climate change for the distribution of the water opossum (Chironectes minimus): habitat loss and conservation opportunities - Roniel Freitas-Oliveira; Wellington Hannibal; Matheus S. Lima-Ribeiro; Levi Carina Terribile (Mammalian Biology, 2021)

Impacts of a hydroelectric power plant on the bat community in central Brazil - Marlon Zortéa; Karla de Souza Gomes; Leonardo Aparecido Guimarães Tomaz; Jorge M. M. M. Palmeirim; Matheus S. Lima-Ribeiro (Mammal Research, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Evaluating the impact of future actions in minimizing vegetation loss from land conversion in the Brazilian Cerrado under climate change - Lara M. Monteiro; Fernanda Thiesen Brum; Robert L. Pressey; Leonor Patricia C. Morellato; Britaldo Soares-Filho; Matheus S. Lima-Ribeiro; Rafael Loyola (Biodiversity and Conservation, 2020)

Climatic changes can drive the loss of genetic diversity in a Neotropical savanna tree species - Jacqueline S. Lima; Liliana Ballesteros‐Mejia; Matheus S. Lima‐Ribeiro; Rosane G. Collevatti (Global Change Biology, 2017)
The high rates of future climatic changes, compared with the rates reported for past changes, may hamper species adaptation to new climates or the tracking of suitable conditions, resulting in significant loss of genetic diversity. Trees are dominant species in many biomes and because they are long‐lived, they may not be able to cope with ongoing climatic changes. Here, we coupled ecological niche modelling ( ENM ) and genetic simulations to forecast the effects of climatic changes on the genetic diversity and the structure of genetic clusters. Genetic simulations were conditioned to climatic variables and restricted to plant dispersal and establishment. We used a Neotropical savanna tree as species model that shows a preference for hot and drier climates, but with low temperature seasonality. The ENM predicts a decreasing range size along the more severe future climatic scenario. Additionally, genetic diversity and allelic richness also decrease with range retraction and climatic genetic clusters are lost for both future scenarios, which will lead genetic variability to homogenize throughout the landscape. Besides, climatic genetic clusters will spatially reconfigure on the landscape following displacements of climatic conditions. Our findings indicate that climate change effects will challenge population adaptation to new environmental conditions because of the displacement of genetic ancestry clusters from their optimal conditions.

Spatial autocorrelation analysis and ecological niche modelling allows inference of range dynamics driving the population genetic structure of a Neotropical savanna tree - José Alexandre F. Diniz‐Filho; Ana Clara O. F. Barbosa; Rosane G. Collevatti; Lázaro J. Chaves; Levi Carina Terribile; Matheus S. Lima‐Ribeiro; Mariana P. C. Telles (Journal of Biogeography, 2016)
Aim Spatial autocorrelation analysis of genetic diversity was combined with ecological niche modelling ( ENM ) to better infer how ecological and evolutionary processes underlie population structure in Eugenia dysenterica, a widely distributed tree in the ‘Cerrado’ region of Central Brazil. Location ‘Cerrado’ region, Central Brazil. Methods Data were derived from 11 microsatellite loci in 23 populations of E. dysenterica , totalling 249 allele frequencies. The expected heterozygosity ( He ) within populations and the first principal coordinates extracted from pairwise F ST and from the difference between R ST and F ST among populations were correlated with shifts in suitability from ENM . Frequencies were then analysed using a spatial autocorrelation analysis based on Moran's I and Mantel tests to contrast population differentiation for mean allele frequencies, allele size and shifts in suitability since the Last Glacial Maximum inferred from ENM . Results Spatial correlograms based on Moran's I and Mantel tests showed a linear decrease in autocorrelation with distance, which revealed north‐west–south‐east gradients in allele frequencies, genetic diversity and differences between R ST and F ST . These spatial patterns varied among loci and alleles, and the strongest spatial patterns were found for more common alleles with higher levels of differentiation among populations and for those correlated with shifts in ENM suitability. Main conclusions Current genetic diversity and population structure in E. dysenterica can be explained by geographical range shifts associated with Quaternary climate dynamics, thus demonstrating the value of applying spatial analyses to study the ecological and evolutionary processes underlying differentiation even within populations possessing a continuous distribution.

Biogeography of Neotropical Rainforests: past connections between Amazon and Atlantic Forest detected by ecological niche modeling - Thadeu Sobral-Souza; Matheus S. Lima-Ribeiro; Vera Nisaka Solferini (Evolutionary Ecology, 2015)

Phylogeography and ecological niche modelling, coupled with the fossil pollen record, unravel the demographic history of a Neotropical swamp palm through the Quaternary - Natácia Evangelista de Lima; Matheus S. Lima‐Ribeiro; Carla Faleiro Tinoco; Levi Carina Terribile; Rosane G. Collevatti (Journal of Biogeography, 2014)
Aim The recovery of demographic history through phylogeographical analysis is critical for understanding microevolutionary processes and the spatial/temporal context of lineage divergence. Palaeodistribution modelling and the fossil record might provide the spatial context for statistical phylogeographical analyses, allowing the generation of independent palaeoscenarios of demographic history that can be tested using coalescent models. In this study we generated independent demographic scenarios to examine geographical barriers to gene flow in a Neotropical swamp palm, Mauritia flexuosa , and assessed how climatic changes during the Pleistocene influenced its geographical distribution and genetic diversity. Location Neotropical wetlands. Methods We sampled 257 adult individuals of M. flexuosa from 26 localities in the Amazon, Araguaia/Tocantins, Paraguai, Paraná and São Francisco basins. The analyses were based on statistical phylogeography, ecological niche modelling and the fossil pollen record. The genetic data were based on polymorphisms in three chloroplast non‐coding regions. Results Mauritia flexuosa presented low genetic diversity but significant genetic differentiation among populations from different river basins. The ecological niche modelling and demographic simulations showed that the pattern of observed genetic diversity for M. flexuosa probably reflects range retraction during the Last Glacial Maximum, leading to multiple refugia. In support of this, the fossil pollen record suggests that multiple refugia were present in Brazilian savannas, where M. flexuosa often disappeared during cold and dry periods across the last glacial cycle, returning during the wet phases. The periodic dryness in this region was driven by the latitudinal displacement of the Intertropical Convergence Zone (ITCZ) across glacial/interglacial periods, which possibly affected the distributional dynamics of M. flexuosa during the Pleistocene epoch. Main conclusions Our results provide evidence that climate changes during the last glacial cycle were important determinants of the geographical distribution and demographic history of M. flexuosa across the late Quaternary period. In addition to the geographical barriers imposed by river basins, these factors have shaped genetic differentiation, as currently observed among lineages.

Drawbacks to palaeodistribution modelling: the case of South American seasonally dry forests - Rosane G. Collevatti; Levi Carina Terribile; Guilherme de Oliveira; Matheus S. Lima‐Ribeiro; João C. Nabout; Thiago F. Rangel; Jose Alexandre F. Diniz‐Filho (Journal of Biogeography, 2013)
Aim Species distribution modelling ( SDM ) has increasingly been used to predict palaeodistributions at regional and global scales in order to understand the response of vegetation to climate change and to estimate palaeodistributions for the testing of biogeographical hypotheses. However, there are many sources of uncertainty in SDM that may restrict the ability of models to hindcast palaeo‐distributions and provide a basis for hypothesis testing in molecular phylogenetics and phylogeographical studies. Location Seasonally dry forests (SDFs) in South America. Methods We addressed the problem of using palaeodistribution modelling for SDF s based on the projection of their current distribution into past environments (21 ka) using 11 methods for SDM s and five coupled atmosphere–ocean global circulation models ( AOGCM s) for 16 species. Results We observed considerable uncertainty in the hindcasts, with the most important effects for AOGCM (median 12.2%), species (median 15.6%) and their interaction (median 13.6%). The effects of AOGCM s were stronger in the Amazon region, whereas the species effect occurred primarily in the dry areas of central Brazil. The log‐linear model detected significant effects of the three sources of variation and their interaction on the classification of each map in supporting alternative hypotheses. An expansion scenario combining the Pleistocene arc and Amazonian expansion, and Pennington's Amazonian expansion alone, were the most frequently supported palaeodistribution scenarios. Main conclusions As a basis for evaluating a given hypothesis, hindcast distributions must be used in direct association with other evidence, such as molecular variation and the fossil record. We propose an alternative framework concerning hypothesis testing that couples SDM and phylogeographical work, in which palaeoclimatic distributions and other sources of information, such as the pollen fossil record and coalescence modelling, must be weighted equally.

A coupled phylogeographical and species distribution modelling approach recovers the demographical history of a N eotropical seasonally dry forest tree species - Rosane G. Collevatti; Levi Carina Terribile; Matheus S. Lima‐Ribeiro; João C. Nabout; Guilherme de Oliveira; Thiago F. Rangel; Suelen G. Rabelo; Jose A. F. Diniz‐Filho (Molecular Ecology, 2012)
We investigated here the demographical history of T abebuia impetiginosa ( B ignoniaceae) to understand the dynamics of the disjunct geographical distribution of S outh A merican seasonally dry forests ( SDF s), based on coupling an ensemble approach encompassing hindcasting species distribution modelling and statistical phylogeographical analysis. We sampled 17 populations (280 individuals) in central B razil and analysed the polymorphisms at chloroplast ( trn S ‐trn G , psb A ‐trn H , and ycf6‐trn C intergenic spacers) and nuclear ( ITS nr DNA ) genomes. Phylogenetic analyses based on median‐joining network showed no haplotype sharing among population but strong evidence of incomplete lineage sorting. Coalescent analyses showed historical constant populations size, negligible gene flow among populations, and an ancient time to most recent common ancestor dated from ~4.7 ± 1.1 Myr BP. Most divergences dated from the L ower P leistocene, and no signal of important population size reduction was found in coalescent tree and tests of demographical expansion. Demographical scenarios were built based on past geographical range dynamic models, using two a priori biogeographical hypotheses (‘ P leistocene A rc’ and ‘ A mazonian SDF expansion’) and on two additional hypotheses suggested by the palaeodistribution modelling built with several algorithms for distribution modelling and palaeoclimatic data. The simulation of these demographical scenarios showed that the pattern of diversity found so far for T . impetiginosa is in consonance with a palaeodistribution expansion during the last glacial maximum ( LGM , 21 kyr BP), strongly suggesting that the current disjunct distribution of T. impetiginosa in SDF s may represent a climatic relict of a once more wide distribution.